Key to Improving Postpartum Contraception Services - Untung Gunawan; Mellysa Wulandari Taspirin; Intan Rina Susilawati; Ernawati (Jurnal Kesehatan Metro Sai Wawai, 2025)
Postpartum contraceptive services plays an important role in reducing the rate of unplanned pregnancies and improving maternal and child health. However, its coverage in Indonesia is still low. This study aims to evaluate the quality of postpartum contraception services through three aspects: technical, functional, and accessibility. The study design is quantitative descriptive-analytical, with respondents being reproductive-age women who have given birth and accessed contraception services in 2024. Data were collected through a questionnaire survey and analyzed using chi-square tests and logistic regression. The results indicate that the quality of services is a dominant factor in the use of modern contraceptives, particularly among millennial women (OR = 18.6). Technical aspects such as method availability and staff competence, as well as functional aspects such as attitude, clarity of information, and privacy significantly influence patient decisions. Although accessibility was not statistically significant, economic factors and distance remain practical barriers. This study recommends improving service quality, training healthcare workers, and developing community-based service models to expand access to quality contraception in Indonesia.